Komunikasi Dakwah Di Lingkungan Karang Taruna Desa Sindanglaya Dalam Pembentukan Karakter Generasi Muda - Ruswandi, Hendri (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2017)
The formation of character for the younger generation is very important for the successors of the nation and state, with the formation of character for the younger generation it can be an example for the local community, because of that the researchers carried out research on Communication of Da'wah Karang Taruna in Sindanglaya Village in Formation of Character for the Young Generation. The type of research used is qualitative research with a method of communication approach and psychology. There are two sources of data in this study, namely primary data sources and secondary data sources. Primary data sources include several informants including the Youth Organization Leader. Village Government, Youth Organization Members, Community Leaders. While secondary resources are in the form of interviews, documentation tools, and writing tools. The results of this study indicate that the forms of communication applied by youth organizations in character building are lecture training, basic leadership training training, and the movement to commemorate independence day. In the formation of this character, youth organizations can be the successors for the nation and state. Moreover, the youth organizations in Sindanglaya village can be an example for the next generation. Each activity has internal performance factors from the Karang Taruna leadership, human resources (HR), and funds. While external factors, namely, participation from the village government, the influence of relationships outside the village area, and parental support.